Impacts of delivery mode on very low birth weight infants’ oral microbiome - Hongping Li; Yong Zhang; Bin Xiao; Shanqiu Xiao; Jiaman Wu; Weimin Huang (Pediatrics and Neonatology)
Objectives: Initial microbial colonization of the oral after birth provides a vital stimulus for neonatal immune and development. The establishment of the gut microbiota has been shown to differ between very low birth weight (VLBW) infants delivered by caesarian section (C-section) and those delivered vaginally. The objective of this study was to investigate the community structure of the oral microbiota in VLBW infants delivered by the two modes. Methods: In total, 23 VLBW infants who were hospitalized in the neonatal intensive care unit of Shenzhen BaoAn Maternity & Child Health care Hospital (Shenzhen, China) were recruited for this study: 12 infants delivered vaginally, and the other 11 infants delivered by C-section. The assessment of oral microbiota community was performed using 16S rRNA gene sequence analysis. Results: The results demonstrated that the oral bacterial communities were dominated by the phylum Proteobacteria in both groups. Higher relative abundance of genera Ureaplasma and Pantoea were observed in the vaginal delivery infants, but genera Corynebacterium, Methylobacterium and Variovorax were more prevalent in cesarean-born infants. Furthermore, many metabolic pathways with significant differences between the two groups were detected, mostly related to vitamin, amino acid metabolism and diseases. Additionally, ɑ-diversity and clinical data showed no significant differences between the two groups. Conclusions: This study indicated that the mode of delivery influences the oral bacterial structure of VLBW infants after birth, but the consequences for neonatal development should be researched in a further study. Key Words: oral microbiota, very low birth weight infants, the mode of delivery, 16s rRNA gene sequencing